2007
DOI: 10.1159/000111143
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Localization and Higher Ultrafiltration Rate but Not Concentration of Heparin Used for Canal Locking of Hemodialysis Catheter Are Negative Predictors for Its Malfunction

Abstract: Background/Aim: Non-tunneled, temporal hemodialysis (HD) catheters are commonly used as short-term vascular access for the HD procedure. One of their late complications is thrombotic occlusion of the catheter ensuing in their malfunction. A heparin lock is conventionally used for maintaining the patency of the catheter. The aim of the study was to evaluate the influence of heparin concentration used for locking the catheter canals (5,000 vs. 2,500 IU/ml) and some other clinical and laboratory variables at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…According to the obtained results, the risk of catheter thrombosis was equal between both groups but we have to bear in mind that the observation period in our study was just 24 h. Noteworthy, it may be speculated based on earlier data that heparin at a concentration from 1,000 to 2,500 IU/ml is equally effective as heparin used at a higher concentrations in prevention of catheter thrombosis [9, 12]. Thus, it seems that with lower heparin concentration the same catheter patency is obtained.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…According to the obtained results, the risk of catheter thrombosis was equal between both groups but we have to bear in mind that the observation period in our study was just 24 h. Noteworthy, it may be speculated based on earlier data that heparin at a concentration from 1,000 to 2,500 IU/ml is equally effective as heparin used at a higher concentrations in prevention of catheter thrombosis [9, 12]. Thus, it seems that with lower heparin concentration the same catheter patency is obtained.…”
Section: Discussionmentioning
confidence: 68%
“…It was shown earlier [9] that heparin concentration did not adversely affect catheter patency. The aim of the study was to test a hypothesis that the lower heparin concentration used for canal locking limits bleeding episodes in HD after PC insertion.…”
Section: Introductionmentioning
confidence: 82%
“…The heparin concentration used for locking has been reduced because catheter lumens have increased in volume so as to reduce the possibility of unintentional systemic anticoagulation of patients (26 -29). Locking with lower heparin concentrations (2500 or 1000 U/ml) prevents catheter thrombosis as efficiently as 5000 U/ml (30,31). Heparin loss ("leak phenomenon") through diffusion from the lumen within the first hour or after injecting the locking solution (slow versus fast) may accidentally administer up to half the anticoagulant systemically (27) and may explain reports of bleeding episodes after heparin lock (32,33).…”
Section: Maintaining Patency With Catheter Locking Solutions Between mentioning
confidence: 99%
“…The lower blood flows (150–250 ml/minute) might be adequate for CRRT and the HDC can be used until the patient is more stable to be switched to IHD. One recent study of temporary HDCs showed that femoral localization was associated with a higher risk for thrombosis, when compared to the IJ site (6).…”
Section: Complicationsmentioning
confidence: 99%